2020
DOI: 10.1016/j.ymgmr.2020.100625
|View full text |Cite
|
Sign up to set email alerts
|

Targeted next generation sequencing for newborn screening of Menkes disease

Abstract: Purpose Population-based newborn screening (NBS) allows early detection and treatment of inherited disorders. For certain medically-actionable conditions, however, NBS is limited by the absence of reliable biochemical signatures amenable to detection by current platforms. We sought to assess the analytic validity of an ATP7A targeted next generation DNA sequencing assay as a potential newborn screen for one such disorder, Menkes disease. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…In this study, seven patients were diagnosed and treated in the neonatal period, and all of them were diagnosed based on the family history but not symptoms. It is also true that almost all patients who were treated from the neonatal period were diagnosed based on the family history but not symptoms, consistent with the results reported by Kaler et al [ 10 ] and Parad et al [ 30 ]. These findings suggest that neonatal mass screening is needed for this disease.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, seven patients were diagnosed and treated in the neonatal period, and all of them were diagnosed based on the family history but not symptoms. It is also true that almost all patients who were treated from the neonatal period were diagnosed based on the family history but not symptoms, consistent with the results reported by Kaler et al [ 10 ] and Parad et al [ 30 ]. These findings suggest that neonatal mass screening is needed for this disease.…”
Section: Discussionsupporting
confidence: 89%
“…Some patients exhibited near-normal neurodevelopment and neurological functions [ 9 , 10 ]. Moreover, the effect of early treatment may be dependent on the type of mutations in ATP7A [ [28] , [29] , [30] ]. Splice-site mutations and missense mutations display high sensitivity to early treatment, whereas the response of patients with missense mutations appears to be dependent on the effect of the mutation on the ATP7A structure [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Various sequencing approaches are increasingly used in NBS algorithms for second-tier confirmation, and the use of sequencing has been proposed as an alternative primary method of detection. 10 Though a number of studies have demonstrated the ability of ES/GS to diagnose genetic conditions in symptomatic infants, [11][12][13][14] prior comparisons of traditional NBS with ES/GS have shown that infants may be missed by either method, though these analyses generally favor traditional NBS as more sensitive than ES/GS for the RUSP-targeted disorders. [15][16][17] There are relatively few studies comparing the results of ES/GS to NBS in a cohort that is not enriched for such disorders, with one prior study demonstrating a higher sensitivity of conventional NBS versus ES to detect NBStargeted conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Commercially available targeted–sequencing tests can interrogate a finite number of genes associated with specific genetic disorders. These panels are less expensive than genomic sequencing, return results faster, and rarely identify secondary findings . A comparative analysis between genomic sequencing and a targeted neonatal gene-sequencing test has not been previously performed …”
Section: Introductionmentioning
confidence: 99%